Anxiety Level in Dyspeptic Patients at the Gastroenterohepatology Outpatient Clinic of Dr. Hasan Sadikin General Hospital Bandung, Indonesia - Radistrya Sekaranti Brahmanti; Juke Roslia Saketi; Harry Saroinsong; Primal Sudjana (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Dyspepsia is a disease with a high worldwide prevalence, including in Asia; however, the pathophysiology of the disease is still unclear. Recent studies suggest adapting a biopsychosocial model to understand the pathophysiology of dyspepsia that proposes the important role of anxiety. The aim of this study was to assess the anxiety level in dyspeptic patients who visited the Gastroenterohepatology Outpatient Clinic in Dr. Hasan Sadikin General Hospital Bandung. Methods: A cross-sectional descriptive study using total sampling method was conducted from September–November 2012 to 19 patients aged 36−85 years old who consisted of 11 women and 8 men patients dyspepsia syndrome in the Gastroenterohepatology outpatient clinic Dr Hasan Sadikin General Hospital Bandung. The anxiety levels were measured using the Zung Self-Rating Anxiety Scale. All data were analyzed based on gender, age, and occupational status of the patients. Results: Eleven of the nineteen patients had high anxiety levels. Women were more likely to experience high anxiety levels (8 of 11). The group with the highest number of patients with high anxiety was the 46−55 years old group, the high anxiety level was more common among patients who were government or private sector employees. Conclusion: The anxiety level in dyspeptic patients who visited the Gastroenterohepatology outpatient clinic in Dr. Hasan Sadikin General Hospital Bandung was high.Keywords: Anxiety levels, Dyspeptic patients, Zung Self-Rating Anxiety Scale DOI: 10.15850/amj.v2n1.429